2014
DOI: 10.1007/s10661-014-4173-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioremoval of heavy metals by bacterial biomass

Abstract: Heavy metals are among the most common pollutants found in the environment. Health problems due to the heavy metal pollution become a major concern throughout the world, and therefore, various treatment technologies such as reverse osmosis, ion exchange, solvent extraction, chemical precipitation, and adsorption are adopted to reduce or eliminate their concentration in the environment. Biosorption is a cost-effective and environmental friendly technique, and it can be used for detoxification of heavy metals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(37 citation statements)
references
References 138 publications
0
37
0
Order By: Relevance
“…It was also reported that NaOH stress increases the binding of toxins by bacteria cell surfaces (Aryal & Liakopoulou‐Kyriakides, ; El‐Nezami et al, ). In this study, the mechanism behind the increase in absorption of B[a]p after 1‐hr exposure with NaOH was observed because NaOH can hydrolyze amide and ester carboxyl groups of the bacterial cell wall, as a result, more binding sites were exposed to a certain extent.…”
Section: Resultsmentioning
confidence: 97%
“…It was also reported that NaOH stress increases the binding of toxins by bacteria cell surfaces (Aryal & Liakopoulou‐Kyriakides, ; El‐Nezami et al, ). In this study, the mechanism behind the increase in absorption of B[a]p after 1‐hr exposure with NaOH was observed because NaOH can hydrolyze amide and ester carboxyl groups of the bacterial cell wall, as a result, more binding sites were exposed to a certain extent.…”
Section: Resultsmentioning
confidence: 97%
“…Most heavy metals can be passively adsorbed onto anionic functional groups present in external polysaccharides (EPS) and membrane lipids and proteins (Kikuchi and Tanaka, 2012), like peptidoglycan, phospholipids, lipopolysaccharides, teichuronic and teichoic acids and various proteins (Vijayaraghavan and Yun, 2008; Din et al, 2014). The sorption potential of heavy metals depends on pH, biomass loading, equilibrium time, initial metal ion concentration, temperature, and the method of the sorption process applied (Aryal and Liakopoulou-Kyriakides, 2015). Even precious metals like Au can bind onto EPS of bacteria (Colica et al, 2012).…”
Section: Resource Recovery For a Circular Economymentioning
confidence: 99%
“…Sometimes, complex synthesis of exchangers is essential [12][13][14][15][16]. These methods have multiple disadvantages, including high cost, low efficiency, and re-contamination due to the generation of toxic matter [17][18][19]. Bacteria are comparatively more effective for toxic metal adsorption, specifically at low concentrations of heavy metals in solutions [20][21][22].…”
Section: Introductionmentioning
confidence: 99%